Evaluation of Accumulation ability for Pb, Cr, Ni, and Mn in Native Plants Growing on a Contaminated Air Force Shooting Range, Kaduna (Global Journal of Science Frontier Research, 2015)
The concentrations of Pb, Cr, Ni and Mn were determined in Sida veronicifolia, Chrystanthelum americanum, Cassia rotundifolia and Borreria filifolia samples using Atomic Absorption spectrophotometry at the Air Force shooting range, Kaduna. The heavy metals (Pb, Cr, Ni and Mn) concentrations in Borreria filifolia shoot were found to be (229.29 ± 0.03, 33.26 ± 0.00, 200 ± 0.01, and 142.51 ± 0.01 mg/kg respectively while those of Sida veronicifolia samples in shoot are 189.27 ± 0.04, 170.56 ± 0.03, 111.9 ± 0.04 and 158.71 ± 0.01 mg/kg respectively for Pb, Cr, Ni and Mn. In chrystanthelum americanum samples in shoot are found 112.31 for Pb, 41.14 ± 0.01 mg/kg for Cr, 176.64 ± 0.00 mg/kg of Ni and 228.80 ± 0.02 mg/kg of Mn. Cassia rotundifolia gave 112.23 ± 0.00 mg/kg for Pb, 41.09 ± 0.01 mg/kg for Cr, 176.56 ± 0.05 mg/kg for Ni while 228.71 ± 0.03 mg/kg in Mn. The translocation factor (TF) indicates that the plants accumulated these metals (Cr, Ni and Mn) more in the shoots than in the roots. S. veronicifolia and B. filifolia can be used to decontaminate soil contaminated with (Cr and Mn) studied because TF is greater than one (TF > 1) while other plants can only be used for decontamination of soil polluted with selected metals where (TF>1).
Keywords: heavy metals; shooting range; translocation factor and native plants